European Pain Federation position paper on appropriate opioid use in chronic pain management - O'Brien, Tony; Mikus, Gerd (European journal of pain, 2017)
Poorly controlled pain is a global public health issue. The personal, familial and societal costs are immeasurable. Only a minority of European patients have access to a comprehensive specialist pain clinic. More commonly the responsibility for chronic pain management and initiating opioid therapy rests with the primary care physician and other non-specialist opioid prescribers. There is much confusing and conflicting information available to non-specialist prescribers regarding opioid therapy and a great deal of unjustified fear is generated. Opioid therapy should only be initiated by competent clinicians as part of a multi-faceted treatment programme in circumstances where more simple measures have failed. Throughout, all patients must be kept under close clinical surveillance. As with any other medical therapy, if the treatment fails to yield the desired results and/or the patient is additionally burdened by an unacceptable level of adverse effects, the overall management strategy must be reviewed and revised. No responsible clinician will wish to pursue a failed treatment strategy or persist with an ineffective and burdensome treatment. In a considered attempt to empower and inform non-specialist opioid prescribers, EFIC convened a European group of experts, drawn from a diverse range of basic science and relevant clinical disciplines, to prepare a position paper on appropriate opioid use in chronic pain. The expert panel reviewed the available literature and harnessed the experience of many years of clinical practice to produce these series of recommendations. Its success will be judged on the extent to which it contributes to an improved pain management experience for chronic pain patients across Europe. Significance: This position paper provides expert recommendations for primary care physicians and other non- specialist healthcare professionals in Europe, particularly those who do not have ready access to specialists in pain medicine, on the safe and appropriate use of opioid medications as part of a multi-faceted approach to pain management, in properly selected and supervised patients.
Gesehen am 04.01.2017